Numerical and experimental collapse analysis of tubular multi-member energy absorbers under lateral compression - Lipa, Sebastian; Kotełko, Maria (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2004)
In the paper, the problem of collapse load and energy dissipation capacity of tubular multi-member energy absorbers subject to lateral crushing load is presented. The method of analytical solution of the problem of initial collapse load and load capacity at failure both for single-member and multi-member absorbers is discussed. A numerical Finite Elelment (FE) model of the multi-member absorber is presented and the parametric study of the influence of different absorber parameters (number of members, thickness of tubes, configuration of tubes) upon the collapse load and energy dissipation capacity is carried out. Results of numerical calculations are compared with those obtained from the experiment conducted by the authors. Both numerical and experimental results are presented in the form of load-deformation diagrams and diagrams of deformation patterns. Some final conclusions concerning the usefulness of multi-member tubular absorbers and indications into further investigations are derived.

Artykuł przedstawia zagadnienia nośności w fazie zniszczenia i zdolności rozproszenia energii, wieloczłonowych, rurowych absorberów energii poddanych bocznemu zgniotowi. Zaprezentowane zostały metody analizy wstępnej fazy zniszczenia i ilości energii dysypowanej przez absorber jedno- i wieloczłonowy. Przedstawiono numeryczny model elementów skończonych (FE) absorberów wieloczłonowych, jak również omówiono wpływ różnych parametrów absorbera, takich jak ilość członów, grubość elementów rurowych oraz konfiguracja tych elementów na fazę zniszczenia i ilość energii dysypowanej. Wyniki obliczeń numerycznych zostały porównane z wynikami uzyskanymi przez eksperyment autorów. Zarówno wyniki numeryczne, jak i eksperymentalne są przedstawione w formie wykresów obciążenia - odkształcania i map odkształceń. Przedstawiono konkluzje dotyczące zastosowania wieloczłonowych absorberów rurowych oraz wskazówki do dalszych badań.
Numeryczna i eksperymentalna analiza zniszczenia rurowych wieloczłonowych absorberów energii poddanych bocznemu zgniotowi
Keywords: impact crashworthiness; crushing load; energy dissipation; tubular energy absorbes; zagadnienie nośności; nośność; rozproszenie energii; numeryczna analiza; boczny zgniot; model elementów skończonych; absorbeny wieloczłonowe; obliczenia numeryczne; mapy odkształceń; wieloczłonowe absorbeny rurowe